Using time-out to treat advanced stuttering - Franklin, Diane E. (Curtin University, 2002)
This study involved trialing an operant conditioning procedure known as time-out, as a treatment for adolescents and adults who stutter. Time-out requires individuals to pause briefly after stuttering and to resume talking after a pause in this case, of five seconds. A randomised control group design was used to evaluate the effectiveness of time-out treatment. Sixty participants were randomly assigned to either a time-out treatment or control group. The results demonstrated that individuals who stutter are highly responsive to time-out treatment. The impact of the severity of the stutter, a person's age, previous treatment, and the nature of the stutter on treatment outcome, were also investigated. Baseline severity was a strong predictor of treatment outcome, and to a lesser degree, previous treatment and speech rate were found to share some influence over treatment success. In addition, there was an unexpected change in the stuttering topography over the experiment conditions.